2007
DOI: 10.1021/es062693a
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Cape Cod Bacteria Injection Experiment Using a Stochastic Modeling Approach

Abstract: Bromide and resting-cell bacteria tracer tests carried out in a sand and gravel aquifer at the USGS Cape Cod site in 1987 were reinterpreted using a three-dimensional stochastic approach and Lagrangian particle tracking numerical methods. Bacteria transport was strongly coupled to colloid filtration through functional dependence of local-scale colloid transport parameters on hydraulic conductivity and seepage velocity in a stochastic advection-dispersion/attachment-detachment model. Information on geostatistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 42 publications
1
40
0
2
Order By: Relevance
“…However, numerical models have been used to investigate colloid transport in larger two-and three-dimensional systems (e.g. [34,41,4,25,27,2,3,28,36]). These studies suggest that field scale heterogeneities are important in determining the mobility of viruses and colloids in the subsurface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerical models have been used to investigate colloid transport in larger two-and three-dimensional systems (e.g. [34,41,4,25,27,2,3,28,36]). These studies suggest that field scale heterogeneities are important in determining the mobility of viruses and colloids in the subsurface.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have investigated the transport of colloids at the field scale in more complex 3D numerical simulations and found that coupling the colloid removal rate to spatially varying aquifer permeability improved modeling results (e.g. [34,27,28,36]). These studies, however, assumed an infinite number of sites for colloid retention on the soil surface.…”
Section: Introductionmentioning
confidence: 99%
“…SLIM-FAST has been applied to a range of problems including stochastic risk assessment Siirila et al, 2010], microbial and bacterial transport [Maxwell et al, 2003[Maxwell et al, , 2007, and age distributions of water and isotopic tracers [Tompson et al, 1999;Maxwell et al, 2003;Kollet and Maxwell, 2008;Maxwell et al, 2009]. Within SLIM-FAST, particles may transfer between a mobile and an immobile state by single-rate Markov chains.…”
Section: Appendix B: Numerical Considerationsmentioning
confidence: 99%
“…It was first applied to tracer transport in saturated alluvial formations [Ahlstrom et al, 1977;Prickett et al, 1981], and then porous media of all types [Uffink, 1985;Kinzelbach, 1988;Cordes et al, 1991;Mahinthakumar and Valocchi, 1992;Tompson, 1993;Semra et al, 1993;LaBolle et al, 1996LaBolle et al, , 1998LaBolle et al, , 2000LaBolle and Fogg, 2001;Weissmann et al, 2002;Maxwell et al, 2007;Green, 2010] and extended to fractured rocks with matrix diffusion [Yamashita and Kimura, 1990;Wels et al, 1997;Liu et al, 2000;Tsang and Tsang, 2001;Roubinet et al, 2009Roubinet et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%